ANALISIS SEMIOTIKA PESAN SOSIAL DALAM VIDEO KLIP LAGU "HALU" FEBY PUTRI (The Commercium, 2023)
This studi aims to reveal the social messages contained in the video klip for the song “Halu” Feby Putri. This analysis focuses on the form of depiction of the message contained in each scene, then proceeds to Charles Sanders Peirce's semiotic model (triangle meaning). This research is a qualitative research and uses Charles Sanders Peirce's semiotic analysis. For Charles Sanders Peirce, the fundamental principle of sign nature is representative and interpretive nature. The video clip for the song "Halu" was chosen because the video clip has a lot of social messages aimed at people related to schizophrenia. The results of this study are the social messages contained in the video clip for the song "Halu", namely social values ​​in the form of material values, vital values ​​and spiritual values.